(untitled) (Resunga Journal रेसुङ्गा जर्नल, 2023)
The aim of this article is to explore the situation of Nepal’s foreign trade, its significance, prospects of foreign trade expansion and problems with regard to international trade. The study is based on secondary data, collected from library and internet of last 11 years. Efforts have been made to detect the prospects as well as problems of Nepal’s foreign trade. This study keeps value in promoting foreign trade by finding the various possibilities and problems of Nepal’s foreign trade. It is found that Nepal’s foreign trade suffers from many problems such as open border, landlocked country, lack of trade diversification, high cost of production etc. causing trade deficit and has good prospects in different sectors such as hydro-electric, forest, mineral resources, tourism, etc. to develop and promote foreign trade. Among the various alternatives, diversification of trade in terms of countries and goods is one way to overcome the problems of trade deficit.